Yield response of accessions of Bambara groundnut (Vigna subterranea (L) Verdc) inoculated with Bradyrhizobium japonicum strains - Bitire, Tope Daniel; Abberton, Michael; Oyatomi, Olaniyi; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2023)
Field experiments were conducted in two different agroecological locations, Ibadan and Ikenne in Nigeria, from August through December, during 2019 and 2020 cropping seasons. The studies were set up to reduce reliance on inorganic nitrogen fertilizer and to embrace the use of nitrogen fixing bacteria to improve legume production, so as to increase farmers output and profitability. Precisely, ten accessions of Bambara groundnut (BGN) were used in the trials. Seeds of each BGN accession were coated with each of the following Bradyrhizobium japonicum strains (B. japonicum): FA3, RACA6, USDA110 and IRJ2180A before planting. Also, Nitrogen (N) fertilizer (20kg/ha, urea) was applied to seedlings without inoculation, and an uninoculated control (without inoculation + without fertilization). The experiment is therefore, a factorial arrangement (10 BGN accessions, 4 B. japonicum strains, N fertilizer application, and an uninoculated control). The yield and yield components of inoculated BGN accessions were significantly enhanced at both agroecological locations and seasons. Inoculation of B. japonicum strain, RACA6 strains significantly enhanced the yield and yield component of TVSu-1698 than other inoculated BGN accessions with a mean value of 6234±87 kg ha-1 recorded in both locations and seasons, compared to result obtained in the combination of TVSu-1698 with N fertilizer with a mean value of 3264 ± 943 kg ha-1. Using TVSu-1698 with RACA6 strain, the farmers could get 85% more yield that the average with the other genotypes/strains combination, while an average yield of 60% could be obtained by the farmers for N fertilizer application.